Comparative aspects of cortical neurogenesis in vertebrates. - Cheung, A; Pollen, A; Tavare, A; DeProto, J; Molnár, Z (2007)
The mammalian neocortex consists of six layers. By contrast, the reptilian and avian cortices have only three, which are believed to be equivalent to layers I, V and VI of mammals. In mammals, the majority of cortical cell proliferation occurs in the ventricular and subventricular zones, but there are a small number of scattered individual divisions throughout the cortex. Neurogenesis in the cortical subventricular zone is believed to contribute to the supragranular layers. To estimate the proportions of different forms of divisions in reptiles and birds, we examined the site of proliferation in embryonic turtle (stages 18-25) and chick (embryonic days 8-15) brains using phospho-histone H3 (a G2 and M phase marker) immunohistochemistry. In turtle, only few scattered abventricular H3-immunoreactive cells were found outside the ventricular zone; the majority of the H3-immunoreactive cells were located in the ventricular zone throughout the entire turtle brain. Ventricular zone cell proliferation peaks at stages 18 and 20, before an increase of abventricular proliferation at stages 23 and 25. In turtle cortex, however, abventricular proliferation at any given stage never exceeded 17.5+/-2.47% of the total division and the mitotic profiles did not align parallel to the ventricular zone. Phospho-histone H3 immunoreactivity in embryonic chick brains suggests the lack of subventricular zone in the dorsal cortex, but the presence of subventricular zone in the ventral telencephalon. We were able to demonstrate that the avian subventricular zone is present in both pallial and subpallial regions of the ventral telencephalon during embryonic development, and we characterize the spatial and temporal organization of the subventricular zone. Comparative studies suggest that the subventricular zone was involved in the laminar expansion of the cortex to six layers in mammals from the three-layered cortex found in reptiles and birds. Within mammals, the number of neurons in a cortical column appears to be largely constant; nevertheless, there are considerable differences between the germinal zones in mammalian species. It is yet to be determined whether these elaborations of the subventricular zone may have contributed to cell diversity, tangential expansion or gyrus formation of the neocortex and whether it might have been the major driving force behind the evolution of the six-layered neocortex in mammals.